Prarancangan Pabrik 1-Hexana Dari Etilen Menggunakan Proses Alphahexol Dengan Disain Alat Utama Menara Distilasi O-Xylene - Situmorang, Angela Marici Lisda Elfriyani; Padil, Padil (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
1-Hexene is a raw material in plastic production and classified as a linear alpha olefin compound. 1-Hexane is produced from the ethylene trimerization process. The use of 1hexene in the production of High-density polyethylene (HDPE) and linear low-density polyethylene (LLDPE) is one of the co-monomers. The use of 1-hexane in the manufacture of HDPE and LLDPE is about 2 - 4% and 8 - 10% of the co-monomer. HDPE and LLDPE are used as packaging for food and beverages. The need for 1-hexana in Indonesia is increasing over time, but in Indonesia there is no factory to produces 1-hexene. The increasing need for imports will reduce the source of foreign exchange for the country. So that the establishment of the 1-hexene plant can reduce the need for imports and can increase the country's foreign exchange. The main design is an o-xylene tower which functions to separate o-xylene from the mixture. The type of distillation column used is the tray column. The operating conditions at the distillation column are temperature of 204 °C at the top stage and 270 ° C bars at the bottom stage with pressure at 4 bar respectively. Plant economic analysis is carried out to determine the feasibility of the factory to be built. Based on the results of the economic feasibility analysis of the factory, the 1-hexana plant is feasible to build with a PBB of 2 years, an IRR of 22.7433%, an ROI of 39.388%, and a BEP of 54%. Keywords: 1-Hexene, co-monomer, o-xylene, distillation, economic analysis